THE ETHNOLINGUISTIC SITUATION IN INDRA MUNICIPALITY IN THE RURAL PART OF KRĀSLAVA REGION - Kļavinska, Antra (Via Latgalica, 2008)
The research is based on the processed questionnaire data gathered during the ethnolinguistic expedition to Indra municipality in the rural part of the region of Kraslava in June, 2007 (120 respondents). The paper analyzes the answers of the respondents regarding the ethnic self-identification of the people, their knowledge of languages, the dominance of languages, and their functions in the micro and macro environments of Indra municipality. The most important conclusions are: There is a noticeable difference between the official statistical data and the notions of ethnic belonging of the respondents: the official statistics state that the dominant ethnic group in Indra municipality are Belorussians; however, the major part of respondents consider themselves to be Russians. The Russian language dominates in verbal and written communication in both the micro and the macro environment. Many respondents admit that they speak „their own” language in the municipality - Russian with lexical, morphological and phonetical elements of Belorussian and Polish. The role of the Latgalian language in the rural municipality is not important; the respondents do not see any perspectives for its use in the future. The Latvian language as the official language is respected in the administration of the municipality; however, there is a wish to recognize both Latvian and Russian as official languages. The roles of the school (for the acquisition of the Latvian language) and of the Church (the language of praying is Polish, but masses are held in Russian and Latgalian) are important for the formation of the linguistic scenery of Indra municipality. In the polyethnic and multilingual environment of Indra municipality, there is a predominantly tolerant attitude towards different languages and ethnic groups.